Psychosocial stress based on public speech in humans: is there a real life/laboratory setting cross-adaptation?. (3rd July 2016) - Jezova, D.; Hlavacova, N.; Dicko, I.; Solarikova, P.; Brezina, I.
Abstract: Repeated or chronic exposure to stressors is associated with changes in neuroendocrine responses depending on the type, intensity, number and frequency of stress exposure as well as previous stress experience. The aim of the study was to test the hypothesis that salivary cortisol and cardiovascular responses to real-life psychosocial stressors related to public performance can cross-adapt with responses to psychosocial stress induced by public speech under laboratory setting. The sample consisted of 22 healthy male volunteers, which were either actors, more precisely students of dramatic arts or non-actors, students of other fields. The stress task consisted of 15 min anticipatory preparation phase and 15 min of public speech on an emotionally charged topic. The actors, who were accustomed to public speaking, responded with a rise in salivary cortisol as well as blood pressure to laboratory public speech. The values of salivary cortisol, systolic blood pressure and state anxiety were lower in actors compared to non-actors. Unlike non-actors, subjects with experience in public speaking did not show stress-induced rise in the heart rate. Evaluation of personality traits revealed that actors scored significantly higher in extraversion than the subjects in the non-actor group. In conclusion, neuroendocrine responses to real-life stressors in actors can partially cross-adapt with responses to psychosocial stress under laboratory setting. The most evident adaptation was at the level of heart rate responses. The public speech tasks may be of help in evaluation of the ability to cope with stress in real life in artists by simple laboratory testing.